The effect of static and dynamic eccentricities on the performance of flux reversal permanent magnet machine - Ahlam Luaibi Shuraiji (Institute of Advanced Engineering and Science, 2020)
This study investigates the effect of static and dynamic eccentricities on the performances of flux reversal permanent magnet (FRPM) machine with even rotor pole number, i.e. FRPM machine with 12/10 stator/rotor combination. No-load and load performances of the machine are investigated under three rotor operating conditions including centricity, static eccentricity and dynamic eccentricity. The investigation has been carried out using 2D-FEA. It has been revealed that the 12/10 FRPM machine under normal operating condition has no unbalanced magnetic force, due to the even pole number of the rotor. On the other hand, such undesirable feature would be presented in the 12/10 FRPM machine as a result of the existing of static and dynamic eccentricities. Both static and dynamic eccentric machines exhibit unbalanced three-phase flux linkage as well as back-EMF. Moreover, three operating conditions of the investigated machine have the same fundamental cogging torque harmonic. However, low order harmonics are existed in the static and dynamic centric machines and are not found in the centric machine. Furthermore, about 16% less torque ripple delivered by the centric machine compared with both static and dynamic counterparts.